Analisis Pengaruh Variasi Kecepatan Spindel Terhadap Kekasaran Permukaan Material Scr420h Hasil Pemesinan CNC Turning Mazak Quick Turn Smart 250 - Syahrizal Rafli Ferdian; Jenni Ria Rajagukguk (LPPM Institut Pendidikan Nusantara Global, 2026)
Surface quality is an important parameter in machining processes because it affects component performance, dimensional accuracy, and service life. In CNC turning processes, spindle speed is one of the cutting parameters that significantly influences the surface characteristics of machined components. SCr420H steel is widely used in automotive components requiring high wear resistance and dimensional precision; however, the effect of spindle speed variation on its surface roughness using a Mazak Quick Turn Smart 250 CNC turning machine requires further experimental investigation. This study aims to analyze the effect of spindle speed variations on the surface roughness of SCr420H material and determine the optimum spindle speed based on the lowest roughness value. A quantitative experimental method with a one-factor design was conducted by varying spindle speeds of 1200, 1400, 1600, 1800, and 2000 rpm during the finishing CNC turning process. Other machining parameters were maintained constant, including a feed rate of 0.20 mm/rev, depth of cut of 0.4 mm, VNMG 160404-HQ insert with a 0.4 mm nose radius, and dry machining conditions. Surface roughness measurements were performed using a Surfcom 1800G Surface Roughness Tester to obtain Ra and Rz values. The results showed that spindle speed variations produced a non-linear change in surface roughness. The average Ra values at spindle speeds of 1200–2000 rpm were 3.679 µm, 5.258 µm, 5.942 µm, 5.512 µm, and 3.411 µm, respectively, while the average Rz values were 24.015 µm, 33.640 µm, 36.811 µm, 34.812 µm, and 22.071 µm, respectively. The optimum machining condition was achieved at a spindle speed of 2000 rpm, which resulted in the lowest Ra and Rz values. These findings indicate that proper spindle speed selection can improve the surface quality of SCr420H during CNC turning and provide a reference for determining machining parameters in precision manufacturing processes.